2010
DOI: 10.1111/j.1863-2378.2009.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Nipah Virus Infection in West Kalimantan Province, Indonesia

Abstract: Compared to other viruses, research on Nipah virus has been limited in Indonesia because attributable disease outbreaks have not been reported. However, Nipah virus is a zoonotic Biosafety Level 4 (BSL4) agent, so strategic monitoring is prudent. Farmer interviews and a serologic survey of 610 pig sera and 99 bat sera from West Kalimantan province were conducted. Farmers reported no recent or historic encephalitic or respiratory disease in themselves, their families, workers or pigs. The survey found no eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…Nipah virus has been detected in Pteropid fruit bats in Malaysia, Cambodia, and Thailand by serologic analysis, virus isolation, or RNA amplification,24,26,58 and NiV antibodies have also been detected in fruit bats in Indonesia,25 providing evidence that NiV is endemic to Southeast Asia. The most human cases and deaths of any outbreak to date occurred during the outbreaks in Malaysia and Singapore in 1999, and pigs were the source of human infections, demonstrating the importance of pigs as an intermediary amplification host.…”
Section: Discussionmentioning
confidence: 99%
“…Nipah virus has been detected in Pteropid fruit bats in Malaysia, Cambodia, and Thailand by serologic analysis, virus isolation, or RNA amplification,24,26,58 and NiV antibodies have also been detected in fruit bats in Indonesia,25 providing evidence that NiV is endemic to Southeast Asia. The most human cases and deaths of any outbreak to date occurred during the outbreaks in Malaysia and Singapore in 1999, and pigs were the source of human infections, demonstrating the importance of pigs as an intermediary amplification host.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies demonstrate that Hendra and/or Nipah virus-seropositive fruit bats are widely distributed throughout Asian countries [7-11]. No human cases of henipavirus infection have been reported in Indonesia, although Pteropus vampyrus that are seropositive for both Nipah virus and Hendra virus are distributed nationwide [12,13]. These findings indicate the presence of henipavirus or henipa-like viruses in Indonesian fruit bats, suggesting the need for further epidemiological investigations.…”
Section: Introductionmentioning
confidence: 99%
“…While outbreaks of HeV and NiV have been contained to Australia (HeV) and Malaysia, Bangladesh and India (NiV), additional serological and limited nucleic acid evidence suggests that antigenically related henipaviruses are circulating in other regions including Thailand, Indonesia, China, Madagascar and West Africa [28,29,30,31,32,33,34]. Further serological evidence (cross-reactive antibodies to NiV glycoproteins) has also suggested that henipavirus transmission to domestic pigs in West Africa is possible [35].…”
Section: Introductionmentioning
confidence: 99%